The study of the implementation of OHSAS : 18001 at Kulliyyah of Engineering (KOE) - Wan Yusoff, Wan Ahmad Yusmawiza; Fakhrani, Muhammad; Fairus, Mohd; Adesta, Erry Yulian Triblas (2011)
Purpose-The purpose of this paper is to analyze the impact of awareness towards the implementation of occupational safety and health management system, OHSAS 18001:2004 at Kulliyyah of Engineering, International Islamic University Malaysia (IIUM). Design/methodology/approach- The paper analyzes data from two samples which are 61 staff and 893 students from Kulliyyah of Engineering based on gender, department, years of experience with IIUM, job category and level of study. The problem questions are tested through the analysis. Findings- Data analysis shows that the department, years of experience and job category have direct effect of awareness towards the implementation of the system. Finally, the gender does not show the effect of awareness towards the implementation of the system. Research limitations/implications- Future research should be continuing with the large sample size with different level of difficulty of questions. Moreover, analyses carried out provide some interesting directions and recommendations for future research. Practical implications- The practical implication is continues training needed and implement the system to all departments. Based on the outcome of the analysis, management can review the weaknesses thus make some strategies to overcome them. Indirectly, respondents become aware on the existence of this system from the survey of this paper. Originality/value- the occupational safety and health is not new in engineering field. Basically, this research analyzes the level of awareness among community of KOE. Thus, contribute to the advancement based on the survey questionnaire.